Perspective: the potential of wastewater-based surveillance as an economically feasible game changer in reducing the global burden of pediatric respiratory syncytial virus infection - Thampi, Nisha; Mercier, Elisabeth; Paes, Bosco; Edwards, James O.; Rodgers-Gray, Barry; Delatolla, Robert (Frontiers in Public Health, 2024)
Respiratory syncytial virus (RSV) is the leading viral cause of childhood bronchiolitis and pneumonia causing over 3 million hospitalizations and 100,000 deaths in children under 5 years of age annually. Wastewater-based surveillance (WBS) has proven an effective early warning system for high-consequence pathogens, including SARS-CoV-2, polio, mpox, and influenza, but has yet to be fully leveraged for RSV surveillance. A model predicated on the Canadian province of Ontario demonstrates that implementation of a WBS system can potentially result in significant cost savings and clinical benefits when guiding an RSV preventive program with a long-acting monoclonal antibody. A network of integrated WBS initiatives offers the opportunity to help minimize the devastating global burden of RSV in children by optimizing the timing of preventive measures and we strongly advocate that its benefits continue to be explored.